What is the impact of the adjunctive use of omega-3 fatty acids in the treatment of periodontitis? A systematic review and meta-analysis - Kruse, Anne B. (Lipids Health Dis, 2020)
BACKGROUND: Host modulation therapy has gained increasing interest in periodontal therapy. This systematic review aimed to evaluate the effects of adjunctive administration of omega-3 fatty acids in periodontal therapy. METHODS: The search strategy was determined using the “patient, intervention, comparison, outcome” model. A resulting search term was generated using keywords, and the databases were fed. The databases PubMed, Cochrane Library, and LIVIVO were used. Studies were selected for the literature review based on previously specified inclusion and exclusion criteria. Randomized, controlled, blinded studies, longitudinal studies, comparative studies, and clinical studies were included in the review. Additionally, they used omega-3 fatty acids in the treatment of periodontitis. The following parameters were observed: clinical attachment level (CAL), probing depth (PD), gingival index (GI), bleeding on probing (BOP) and plaque index (PI). A meta-analysis was performed for PD and CAL after 3 months. By analyzing the risk of bias, the validity of the results of each study was demonstrated, and its credibility and quality were assessed. RESULTS: Of 14 studies found, six were included. The results showed a significant reduction in PD and CAL compared to that in the placebo groups in four out of six involved studies, which was confirmed by the meta-analysis. In one study, a significant reduction in BOP was found. GI was significantly reduced in three included studies. PI also showed a significant reduction in three studies. CONCLUSIONS: Within the study limitations, omega-3 fatty acids appear to have a positive effect on periodontal wound healing with regard to reduction in CAL and PD. Based on the results, patients receiving periodontal treatment might benefit from nutritional counseling.